Um estudo sobre as condições de vida e a qualidade do saneamento ambiental local como fatores de interferência para o desenvolvimento de práticas agroecológicas - um estudo de caso - Lopes, Keila Cássia Santos Araújo (2010)
The present study aimed mainly to carry out a mapping of living conditions and quality of environmental sanitation in the Assentamento Horto Loreto, SP.The objective was to determine the outcome of the inter-relation living conditions / local environmental sanitation may be factors affecting the development of agroecological practices in the study area. It also aimed to reconstruct the history of the settlement, through the life trajectories of its residents. To collect the data was used for qualitative and quantitative approaches. Quantitative data were obtained through the application of questionnaires, consisting of thematic blocks, which contain indicators on the quality of environmental sanitation and living conditions, such as schooling, income, source of water supply at home, use of water from various sources, forms of sewage disposal, solid waste disposal, use, storage and disposal of packaging of agricultural chemicals, health care. Qualitative data were obtained by conducting semi-structured interviews, which permits to understand the perception of the settlers regarding their health, environmental and living conditions in the areas of settlement, as well as their expectations of life, dreams and plans. We used univariate statistical analysis and the speech of interviewees for the discussion and analysis of results. The data infer that the population of the settlement is in a vulnerable socio-economic and environmental. Everyday practices undertaken by the settlers have identified that 25% of the settlers use water sources that do not receive treatment for irrigation of food crops, 92.1% use of cesspits and 77.3% opted for burning solid waste, due to lack of garbage collection and 82.9% of farmers use pesticides on their lots. Moreover, it was observed in the settlement low levels of education, as 19.6% of the settlers have only incomplete primary and 36.1% completed elementary school. The income of farmers is another extremely important factor, since 31.4% of farmers survive on one or less than a minimum wage and 20.4% said they have no fixed monthly income. Agroecology is a science that seeks positive interaction between the natural and agricultural ecosystems and to adopt sustainable agricultural practices, or searches for sustainability and socio-economic environment, it is concluded that the daily practices of the settlers, are factors that lead to negative interference in rural areas, preventing the natural resources are in healthy conditions for use in the adoption of farming practices.